Non-intubated anesthetic techniques for thoracic surgery - Coley, Emma Louise; Irons, Joanne Frances (Video-Assisted Thoracic Surgery, 2017)
Non-intubated thoracic surgery is not a new concept, though its use was discontinued with the invention of the double lumen endotracheal tube, and the traditional technique of general anesthesia, muscle relaxation and one-lung positive pressure ventilation became standard. Recent developments in surgical techniques encompassing multi and uniportal video-assisted thoracic surgery in a drive to reduce the operative invasiveness, however, have now allowed us to re-examine our anesthetic technique. This along with advances in anesthetic and monitoring techniques make non-intubated thoracic surgery safer to use by experienced anesthetists. The concept is to maintain spontaneous ventilation and create a surgical pneumothorax providing the operator with a reliable surgical field and reducing the risks associated with intubation and positive pressure ventilation. The technique is gaining popularity and a number of small randomized trials and meta-analyses provide data to suggest that non-intubated surgery is safe and can offer several potential advantages as an alternative to intubation and one-lung positive pressure ventilation. Anesthetic and analgesic techniques vary widely in the published data encompassing a spectrum of consciousness from awake to general anesthesia and utilizing a number of different loco-regional anesthetic techniques and adjuncts. We describe these techniques and expose the common complications and pitfalls in detail in this article. Although experience is still relatively limited, non-intubated techniques are now being used in increasingly complicated patients and surgeries and larger, well-designed studies are now required to establish the preferred techniques, selected patient benefits and the impact on long term outcomes